The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/7964732
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Tendon Excision and Repair for Residual Patella Alta after Prior Failed Patellar Tendon Repair: Surgical Decision Making and Outcome

Abstract: Presented in this report is a complex revision case of a patellar tendon repair preceded by excess tendon excision to correct for recurrent patella alta deformity, in a workers' compensation patient. The goal of this procedure was to alleviate this patient's pain, to preserve his ability to function in his activities of daily living, and to allow him to return to work at some capacity. On postoperative radiographs, the revision procedure appeared to have successfully corrected this patient's patella alta defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…He was later scheduled for wire removal in the right knee but due to COVID affecting attendance, was advised to re-engage with orthopaedics to discuss left tendon revision at a later date. If the left repair does get revised, similar cases have shown good long term recovery with further rehabilitation (10).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…He was later scheduled for wire removal in the right knee but due to COVID affecting attendance, was advised to re-engage with orthopaedics to discuss left tendon revision at a later date. If the left repair does get revised, similar cases have shown good long term recovery with further rehabilitation (10).…”
Section: Discussionmentioning
confidence: 96%
“…His patella tendon length as a ratio of his patella height (insall-salvati ratio) was approximately 2.3, measured objectively using a tape measure. A previous study reported a PTR case required repair when their insall-salvati ratio reached 1.55 [10] whilst [12] defined a repair failure if a tendon displacement reached 11cm. This may indicate a failed repair and coincided with pain developed in the PFJ when contracting his quads in full knee extension -attributed to the patella alta (13,14).…”
Section: Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Despite preventing re-rupture, these fixation devices and the overall construct rarely achieve native motion, especially in flexion [ 8 ]. Improper technique or scarring of the quadriceps or patellar tendon can cause patellar alta or baja, respectively, which can complicate a knee replacement [ 9 , 10 ]. Furthermore, a devastating complication of primary TKA is extensor mechanism disruption, which commonly requires a revision surgery to address, although a previous history of extensor mechanism disruption prior to primary TKA has not been previously evaluated as a risk factor for complication following TKA.…”
Section: Introductionmentioning
confidence: 99%